Nutrient Content of Leaf of Three Selected Tree Species of Flood Plains of Assam, India - Phom, Henchai P. (Indian Journal of Animal Nutrition, 2021)
Livestock plays an important role in sustaining rural livelihood, nutritional and environmental security and growth of Indian Agriculture. Fodder trees are an important feed for livestock, particularly during dry months and flood season when all the other fodder sources have been exhausted. Commonly available fodder tree leaves used as goat forage such as Ficus rumphii and Streblus asper and Litsea monopetela from flood plains of Assam were selected to determine the content of proximate principles, macro- and micro-nutrients and anti-nutritional factors. Considerable variations were observed in the nutrient profile of the studied species. Micro-minerals such as Cu, Zn and Co were lower than required level, while the content of macro-minerals viz., Ca, Mg and P was higher than required level. Saponin was not detected in any of the three species. Based on the nutrient content of the three selected species, it was concluded that either of them can be used as a source of forage for ruminants, especially during the period of scarcity.